Penggunaan Media Gambar dalam Mengatasi Kesulitan Membaca Siswa Kelas II di SD Swasta Islam Nursyamsiani Desa Bintang Meriah Kecamatan Batang Kuis - Nur Andini; Tri Indah Kusumawati; Aufa Yumni (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2024)
This research is entitled "The Use of Image Media in Overcoming Reading Difficulties for Grade II Students at Nursyamsiani Islamic Private Elementary School, Bintang Meriah Village, Batang Kuis District." The objectives are to: 1) Identify the forms of reading difficulties of grade II students; 2) Knowing the effectiveness of image media in overcoming these difficulties; 3) Identify obstacles in the use of image media; and 4) Reveal teachers' efforts in overcoming these obstacles. This research is qualitative-descriptive, involving the principal and homeroom teacher as subjects. Data collection is carried out through observation, interviews, and data analysis. The results of the study showed: 1) Reading difficulties include recognition of similar letters and difficulty in prociting a combination of letters; 2) Image media helps overcome reading difficulties; 3) Constraints include image size, limited facilities, and funds; 4) Teachers' efforts include providing opportunities to see pictures in turns and re-explain the material. This result is expected to encourage an increase in teachers' creativity in the use of learning media to increase interest and effectiveness in learning.